Pengaruh Persepsi Dan Pemahaman Tentang Laporan Keuangan Terhadap Kualitas Laporan Keuangan Pelaku UMKM - Hastuti, Cut Sri Firman; Ariani, Devi; Darmayanti, Cici; Putri, Cut Widy Aulia (Universitas Teuku Umar, 2024)
This research attempts to ascertain how business actors' attitudes and comprehension impact the quality of financial reports in Kecamatan Johan Pahlawan, West Aceh Regency. While presenting comprehensive financial reports is challenging for them because not all business owners have studied accounting in-depth, some MSME actors in Johan Pahlawan District believe that accounting is not that important. All they know is that it records incoming and outgoing cash flows. tief. The general public has very little knowledge of accounting, but businesses of a reasonably big size may afford to hire an accountant or purchase software to make it easier to prepare financial reports that comply with current laws. A quantitative technique was used in this investigation. Primary data from a research sample of ninety-three MSME actors in Kecamatan Johan Pahlawan, West Aceh Regency, was directly gathered via the use of questionnaires by the researchers for the objectives of this study. Multiple linear regression data analysis is the technique employed. Based on the study's findings, Kecamatan Johan Pahlawan, West Aceh Regency's MSME financial reports' quality is significantly influenced by business actors' attitudes and knowledge, with a significant value of 0.000. The quality of MSME financial reports in Johan Pahlawan District, West Aceh Regency, is thus determined by the perception and comprehension of business players, leading to the conclusion that the alternative hypothesis statement (Ha3) is accepted.